Critical dimensions of ethical competence in intercultural religious education: An analysis with special regard to three Scandinavian curricular arenas - Franck, Olof (HTS teologiese studies, 2020)
The central theme in the discussion of how education about religion can, and should, be developed in pluralistic societies concerns challenges and opportunities involving intercultural religious education (RE). One example is Robert Jackson’s report Signposts, commissioned by the Council of Europe, in which various aspects of intercultural competence are captured and made visible regarding a religious didactic context. Here, different dimensions of what can be described as ‘ethical competence’ appear to be central. In this article, the interpretive approach, strongly connected with Jackson, is considered to be in need of a development of a theoretical framing of forceful strategies for handling ethical challenges taking place in multicultural, multireligious and multi-confessional classrooms. It is argued that such strategies will depend on a careful analysis of the concept of ethical competence. A theoretical platform for the argument is presented with reference to James Rest’s analysis of ethical competence, which is shown to be relevant to an examination of how the concept of ethical competence can contribute to the development of strategies for teaching intercultural RE. As a basis for this examination, the Danish, Finnish and Norwegian syllabuses for compulsory school RE are analysed regarding how they express conceptions of ethical competence. This selection shaped the curricular arena of the investigation as being non-confessional, whilst simultaneously, more or less explicitly, resting on a shared historical Protestant anchorage. This twofold interpretation is shown to allow for an analysis of ethical competence, in relation to which an identification of certain prerequisites for developing strategies for teaching intercultural RE is possible.